Reclassification of the plant bug genus Pilophorus in Japan and key to the genera and species of Japanese Pilophorini (Hemiptera: Heteroptera: Miridae: Phylinae) - Yasunaga, Tomohide; Duwal, Ram Keshari; Nakatani, Yukinobu (Zootaxa, 2021)
The Japanese fauna of the myrmecomorphic plant bug genus Pilophorus Hahn is updated and reclassified. Seventeen species are now recognized, including three herein described as new, P. hyotan, P. satoyamanus and P. setulosellus; and P. pullulus Poppius, 1914 which is reinstated as valid and recorded from Japan for the first time. The identity of P. okamotoi Miyamoto & Lee, 1966, originally described from Korean Jeju Island and previously confused with P. satoyamanus n. sp., is reconfirmed and rediagnosed. Frequently misidentified species, P. erraticus Linnavuori, 1962 P. pseudoperplexus Josifov, 1987 and P. setulosus Horváth, 1905 as well as the little known taxon, P. choii, are rediagnosed. The distribution and diagnostic features of P. typicus (Distant, 1909) are presented in light of the recognition of P. hyotan n. sp. An updated checklist and a key to genera and species of the tribe Pilophorini are provided to aid in unequivocal identification of every Japanese pilophorine taxon. A new species of Pherolepis Kulik from Kyushu, P. hizenicus, is also described.